VD_FINDINFO HC / 2011 / 462 vom 19. August 2011 - VD Tribunal cantonal (2011)
REVENU HYPOTHÉTIQUE, OBLIGATION D'ENTRETIEN, VISITE | 163 al. 1 CC, 176 al. 1 ch. 1 CC, 176 al. 3 CC, 273 CC, 274 al. 2 CC